CXCR4 Activation Defines a New Subgroup of Sonic Hedgehog–Driven Medulloblastoma - Sengupta, Rajarshi (2011)
Medulloblastoma prognosis tends to be poor, despite aggressive therapy, but defining molecular subgroups may identify patients who could benefit from targeted therapies. This study used human gene array and associated clinical data to identify a new molecular subgroup of medulloblastoma characterized by coactivation of the Sonic hedgehog (SHH) and CXCR4 pathways. SHH–CXCR4 tumors were more common in the youngest patients where they were associated with desmoplastic histology. In contrast to tumors activating SHH but not CXCR4, coactivated tumors exhibited greater expression of Math1 and cyclin D1. Treatment with the CXCR4 antagonist AMD3100 inhibited cyclin D1 expression and maximal tumor growth in vivo. Mechanistic investigations revealed that SHH activation stimulated CXCR4 cell surface localization and effector signaling activity, whereas SHH absence caused CXCR4 to assume an intracellular localization. Taken together, our findings define a new medulloblastoma subgroup characterized by a functional interaction between the SHH and CXCR4 pathways, and they provide a rationale to clinically evaluate combined inhibition of SHH and CXCR4 for medulloblastoma treatment.